EFEKTIVITAS METODE STAD BERBANTUAN MEDIA AUDIO VISUAL TERHADAP RASA TANGGUNG JAWAB PEMBELAJARAN PAK SISWA KELAS V SD KEBON DALEM SEMARANG - Valentina Bunga Celiana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2022)
Celiana Bunga Valentina.2022. The Effectiveness of the STAD Method Assisted by Audio-Visual Media towards a Sense of Learning Responsibility for PAK Class V Students of SD Kebon Dalem Semarang. Catholic Religious Education and Teaching Study Program, St. Francis Assisi Pastoral College semarang. Supervisor I FR. Wuriningsih, S.Pd, MSc.Ed, and Supervisor II Dr. Hartutik, M.Pd. This research is backgrounded by the low learning outcomes of Catholic Religious Education because the learning activities of students are still monotonous so that the learning of Catholic religious education is less in demand by students. The purpose of this study is to determine the Effectiveness of the STAD Method Assisted by Audio Visual Media against the Sense of Learning Responsibility of PAK Class V Students of SD Kebon Dalem Semarang,. Therefore, students are expected to be active, responsible, and creative in learning Catholic education, the type of research used is Pre-experimental (quantitative) research in the form of One Group Pretest-Postest Design, which is an experiment whose implementation only involves one class as an experimental class without a comparison class. The instruments used at the time of the study were student observation sheets on responsibility, and learning outcomes tests to determine the achievement of student learning outcomes towards Catholic education.